CSR AS THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE IN PT BUMI SERPONG DAMAI TBK - Ernawati, Yuni (Dinasti International Journal of Economics, Finance & Accounting, 2020)
Corporate Social Responsibility as the implementation of Good Corporate Governance at PT Bumi Serpong Damai Tbk. The purpose of this article is to provide a theoretical overview of Corporate Social Responsibility implemented at PT Bumi Serpong Damai by using a descriptive approach to explore and review the implementation of Corporate Social Responsibility through the Community Development program. The implementation of corporate social responsibility which covers the economic, socio-cultural and environmental fields gives a good influence, which is beneficial for the community, the target environment and the company. The Company's Corporate Social Responsibility (CSR) program has also synergized the Company's business efforts with support for the surrounding environment.